Repertório sobre a contenção/movimento do corpo: percepções das professoras da educação infantil sobre a prática corporal em tempos de pandemia - Campos, Sheila Garbulha Tunuchi (Universidade Federal de São Carlos, 2022)
This is a study with greater emphasis on remote teaching in the time of the Covid-19 pandemic, which followed the pandemic moment Covid-19 from contact restriction to the gradual return of classes. Through the qualitative study using a previous questionnaire, we sought to collect general information about the teachers, and the biographical narrative interview, answering the question: During the pandemic, how did the teachers observe their own performance when facilitating physical activities for students in early childhood education via remote learning? Considering the problem, the objectives were outlinedand analyzed based on the following criteria: the biographical narrative interview and the observations made by the four teachers working in early childhood education in relation to the practices of physical activities during remote learning. The study sought to learn what the teachers observe of the family dynamics in relation to the facilitation of physical activities among students while counting on the support of the family to carry out these activities at home. The data were organized in a descriptive and interpretive framework for discussion of the results, using the CSD method (Collective Subject Discourse). The results pointed to the fact that there was a great commitment on the part of the school community to re-assess teaching methodologies with physical activities, which are present at all times in remote teaching; however, at the same time, there was a strong indication methodology inefficiency in regard to teacher training. During the pandemic, families that were actively involved and interacting with the children made all the difference in process once the children returned to in person classes. Not only the teachers, but also the families realized the great relevance of physical activity in early childhood education. It was also observed that physical movement was highly valued in remote teaching, however, not all families satisfactorily adhered to the available proposals, but of those families present, they demonstrated a great contribution to the development of their children, which were observed when in person classes were resumed.
Repertoire on body restraint/movement: perceptions of early childhood education teachers about body practice in times of pandemic
Keywords: Educação infantil; Pandemia; Práticas corporais; Ensino; Education childish; Pandemic; Practices bodily; Teaching; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM